The Role of Female Journalist in Disaster Education in Aceh and North Sumatra - Devi Aghita Arifani; Calya Maharani Putri Yuzerman; Ida Susilowati (CV Insan Kreasi Media, 2026)
Aceh and North Sumatra are among Indonesia’s most disaster-prone regions due to their geographical and climatic conditions. Frequent disasters have triggered humanitarian crises that affect social, psychological, and human security conditions. In this context, the media plays a strategic role in disaster education and in shaping public awareness. From an International Relations perspective, journalists can be seen as non-state actors who contribute to public discourse, promote state accountability, and strengthen human security. This study examines the role of female journalists, particularly Najwa Shihab, in advancing disaster education and public awareness in these regions. Disaster education refers to the dissemination of accurate and context-sensitive information, while public awareness involves fostering empathy, risk understanding, and social responsibility. Using a descriptive qualitative approach, this research relies on literature review and qualitative content analysis. Primary data include interviews, reports, and disaster coverage produced by Najwa Shihab and female journalists, while secondary data are drawn from academic sources. The findings show that female journalists play a significant role in humanizing disaster narratives, amplifying affected communities’ voices, and enhancing public awareness, aligning with both International Relations perspectives and Islamic values on social responsibility.